A case of Pasteurellosis in a hare. - ΤΣΟΥΤΣΑΝΗΣ ΚΩΝ.; ΑΡΤΑΒΑΝΗΣ ΣΠ. (Journal of the Hellenic Veterinary Medical Society, 2019)
In the present paper a case of Pastecerellosis in a hare is described. Pasterella septica has been isolated and it is pointed out the high virulence of this strain